Pengaruh Lokasi dan Kualitas Produk terhadap Keputusan Pembelian - Mohamad Dextra Saputra (Institut Nalanda, 2023)
This research is meant to find out the influence of place and product quality to the purchasing decision at the Central fresh fruit shop Jamanis Tasikmalaya. This research has been conducted due to the fact that the product sale at Central fresh fruit shop Jamanis Tasikmalaya has been decreased for the last one year. Many factors are the cause, one of which is the provision of incomplete products, so that the level of consumer purchases will be lower. The population in this study is all consumers who are making purchases at the jamanis Tasikmalaya fresh central fruit store. The sampling technique used is a non-probability sampling technique, precisely accidental sampling, which is a sample selection technique based on chance, that is, all members of the population who coincidentally meet the researcher can be sampled in the study. The determination of the number of samples used the unknown populations formula and obtained the results of 96 respondents. The results of simultaneous testing using the F test showed that the multiple linear regression model was feasible as a research model. Furthermore, using the t test shows that location has a significant and positive effect on purchasing decisions, while product quality has a significant and positive effect on purchasing decisions. Furthermore, the dominant independent variable towards purchasing decisions is product quality. We recommend that producers of fresh central fruit stores list location points by giving banners or signposts to make them easier to find and must be able to maintain the quality of their fruit products by sorting or separating fruits based on size, maturity level, damage, color, and so on.